Study of Impact of Meteorological Parameters on Atmospheric Transmittance of Solar Radiation over Jumla - Shrestha, Prakash M.; Chapagain, Narayan P.; Karki, Indra B.; Poudyal, Khem N. (Nepal Journal of Science and Technology, 2021)
This paper reports the variation of atmospheric transmittance with meteorological parameters over Jumla (Lat.29.28° N, Long.:82.16° E and Alt.: 2300 m above sea level) from2011 to 2013 (three years) by using CMP6 pyranometer and satellite data. The trends of monthly and seasonal variations of atmospheric transmittance, solar insolation and clearness index have been analyzed. The result exemplifies that during the study period, average value of global solar radiation, solar insolation and clearness index are 19.26 ±3.88 MJ/m2/day , 4.95 ± 1.14 kWh/m2/day and 0.59 ±0.12 respectively. The average value of atmospheric transmittance during the whole study period is 0.60 ± 0.11. The average value of atmospheric transmittance of ozone, Rayleigh scattering, gas mixture, water vapor and aerosol are 0.9830 ±0.0007, 0.8999 ±0.0178, 0.9875 ± 0.0007, 0.8839 ±0.0101 and 0.7836 ±0.0909 respectively. There is positive correlation of relative sunshine hour and negative correlation of rain fall with atmospheric transmittance. Result of this research work is beneficial for the further analysis of solar radiation at different places improving life of flora and fauna and protecting the whole environment.